The Bibliometric Analysis of Bank Stability - Anggaredho, Panji Patra (Master of Management, Faculty of Economics and Business, Diponegoro University, 2024)
The central role of banks in the economy has been getting more attention since the global crisis occurred in 2008 which was caused by the bankruptcy of large banks in the United States. The collapse of the economic system has had implications for high recovery costs so efforts to maintain bank stability must be thought continuously. The studies to analyze literature reviews on the subject of bank stability have never been specifically conducted therefore this study aims to determine and analyze literature mapping on bank stability by meta-data network and studies trends over the last 10 years (2013-2023). We used a literature review study method (a bibliometric analysis approach) to review 165 articles during the observation period. The results of this study shows that studies of bank stability associated with other keywords such as monetary policy, bank profitability, shadow banking, and price stability are still rarely conducted. Then, based on the development of studies trends over 2013-2023 shows a downward trend. This also opens up space for the study of bank stability considering that its existence is needed to prevent a global economic crisis. Furthermore, based on the density visualization, it shows that themes that are rarely associated with bank stability are efficiency, commercial bank, systemic rice, and price stability so these three variables could become study opportunities in the future.